Development of corn silage technology and its financial feasibility for beef cattle in Malaysia - Nazli, Muhamad Hazim (2018)
The Malaysian beef cattle industry has shown a sluggish rate of growth despite the need to reduce imports of over 70% and one of the major limiting factors is the lack of suitable and economic feed. Intensive beef production practised in Malaysia, such as in feedlots, generally rely on the use of available crop by-products such as palm kernel cake (PKC) and imported feed ingredient to complement fodder. An alternative feed that has not been exploited is corn silage, a high-quality feed that is widely used and researched worldwide. In this regard, a series of experiments were done to identify appropriate technologies of corn silage production for the beef cattle industry in Malaysia. The first three experiments were asscociated with the technical aspects of silage making while the fourth study evaluates the financial performance of the technology. In the first experiment, the objective was to determine the optimum harvest stage for making corn silage in terms of yield and quality. An additional objective was to evaluate differences among varieties of corn. Four varieties of corn were harvested at either the silking, milk, dough and dent stages. The results showed that grain corn varieties out performed Malaysia’s widely planted sweet corn variety mainly due to the huge yield difference. Sweet corn dry matter (DM) yield at 15.3 t/ha was significantly lower (P≤0.05) than Suwan, which yielded 28.6 t/ha. Generally, the corn plant was best harvested at the dent stage as the yield was the highest while the quality improved with advanced cob development. Although the crude protein (CP) was the highest at the earlier silking stage (11.4%), the difference was low compared to the dent stage (10.2%). In the second experiment, five different types of silo: i) Mini Bunker, ii) Well, iii) Siloseal, iv) Plastic Drum and v) Plastic Bag were evaluated. All the silo types were successful in producing well fermented silage characterized by a low pH (<4.0). However, the silage quality deteriorated with time after opening with a faster rate of deterioration on the surface layers compared with those at lower depths (P≤0.05). The deterioration rate also varied with the silo type. Plastic Drum was selected as the best silo type based on its superior aerobic stability (more than 21 days), good pH (between 3.2 and 3.7), very low top spoilage rate (0.2 %) and low DM loss (10.8 %). Mini Bunker produced silage with poor aerobic stability and high temperature while Well, Siloseal and Plastic Bag showed some good potential. The third experiment’s objective was to determine the potential of corn silage-based feed in a feeding trial using a beef feedlot system. Comparisons were made among three groups of cattle which were fed respectively with i) corn silage, ii) 50% corn silage plus 50% rice straw or iii) rice straw only as the basal feeds. The feed value and the animal performance showed that corn silage-based diet could produce a good growth rate for beef cattle. The average daily gain (ADG) obtained of 808 g/day from corn silage diet was comparable to cattle fed on conventional PKC/napier grass ration obtained elsewhere. However, the ADG was below that obtained in some other countries signalling potential for improvement. Lastly, all three major components in the corn silage chain: corn plant, corn silage and beef production were tested for their financial feasibility. The analysis showed that both corn plant and corn silage production were financially feasible with net present values (NPV) of RM217,128 and RM373,088 respectively. The calculations were made based on the assumptions developed from the previous experiments and survey done earlier. Only the Plastic Drum was feasible among the silo type with positive NPV of RM373,088. However, the partial budgeting analysis showed that corn silage as feed for beef cattle was not as profitable as conventional feed of PKC with napier grass. The difference in the net benefit per cycle was about 23%. In conclusion, corn silage production was proven to be technically and financially feasible using the technologies developed in the research. Corn silage’s lower profitability than grass/concentrates ration highlight the need for further research in reducing the production cost and determining the best ratio of corn silage to be used in the feed.